2015
DOI: 10.5751/es-07832-200410
|View full text |Cite
|
Sign up to set email alerts
|

How does social support enhance resilience in the trauma-exposed individual?

Abstract: ABSTRACT. Although most resilience science has focused on individual-level psychosocial factors that promote individual resilience, theorists and researchers have begun to examine neurobiological and systems-level factors implicated in resilience. In this commentary we argue that the development of effective interventions to enhance resilience necessitates understanding that resilience in the individual is dependent on multiple layers of society. Further, we suggest that there is a bidirectional relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
202
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(225 citation statements)
references
References 53 publications
(71 reference statements)
14
202
0
9
Order By: Relevance
“…In specific, results show a positive association between resilience and social interaction with colleagues before the beginning of the shift. This finding is consistent with literature showing that social support can promote self‐protection (Shimoinaba, O'Connor, Lee, & Kissane, ) and modifies current behaviours (Sippel, Pietrzak, Charney, Mayes, & Southwick, ). Congruently, Cameron and Brownie () found that colleagues’ support could enhance nurses’ resilience.…”
Section: Discussionsupporting
confidence: 92%
“…In specific, results show a positive association between resilience and social interaction with colleagues before the beginning of the shift. This finding is consistent with literature showing that social support can promote self‐protection (Shimoinaba, O'Connor, Lee, & Kissane, ) and modifies current behaviours (Sippel, Pietrzak, Charney, Mayes, & Southwick, ). Congruently, Cameron and Brownie () found that colleagues’ support could enhance nurses’ resilience.…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, Sippel et al. () state that social networks need to be understood to fully understand resilience in the face of trauma. Empirical studies have begun to confirm this.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple biological and environmental confounders of PCE were assessed and controlled to isolate the effects of PCE and CM, including prenatal exposure to other substances such as alcohol (Larkby et al, 2011), tobacco (Maughan et al, 2004), and marijuana (Goldschmidt et al, 2000), elevated lead (≥10 μg/dL) levels (Lane et al, 2008; Min et al, 2009; Singer et al, 2008), ongoing caregiver postpartum substance abuse (Elkington et al, 2011) and psychological distress (Minnes et al, 2010), poor quality of the home environment (Singer et al, 2008; Min et al, 2014b), and violence exposure (Kobulsky et al, 2016; Frank et al, 2011). Further, lack of ecological resources and support from family, school, and the neighborhood/community which tend to confound with CM (Sippel et al, 2015), were also controlled. We hypothesized that adolescents with PCE would be more reactive to stress (more involuntary engagement and disengagement) and utilize coping strategies less effectively (less primary and secondary control and more disengagement) than adolescents without PCE.…”
Section: Introductionmentioning
confidence: 99%